Security Role in Servicing Visitors at Jakabaring Sport City Palembang - Effendy, Novita Sari; Iryanti, Nurlista (The Future of Education Journal, 2025)
This study examines the role of security personnel in servicing visitors at Jakabaring Sport City, Palembang. As a major sports complex hosting national and international events, Jakabaring Sport City requires effective security measures to ensure the safety and comfort of its visitors. Data collection for this research was conducted from July 1 to August 1, using qualitative methods, including interviews, observations, and surveys. The data were analyzed using three main techniques: (1) Data Reduction, (2) Data Display, and (3) Conclusion Drawing.The findings indicate that security personnel play a vital role not only in managing crowd control and preventing incidents but also in enhancing the overall visitor experience by addressing emergencies promptly. However, the research reveals some areas for improvement in communication between security teams and event organizers, as well as the need for additional training to better handle large-scale events The study suggests several recommendations, including increasing the number of security staff during peak events, improving coordination through regular briefings, and offering specialized training in handling diverse crowds. These enhancements could significantly improve the balance between ensuring safety and providing a positive, welcoming atmosphere for visitors at large sporting venues.